2007
DOI: 10.1002/mrd.20849
|View full text |Cite
|
Sign up to set email alerts
|

Activator protein 1‐mediated expression of monocyte chemoattractant protein 1 in cultured rat luteal cells

Abstract: We have proposed that luteal cells undergo apoptosis-dependent phagocytosis by invading monocyte-derived macrophages in regressive corpora lutea of the rat. Accumulation of monocytes/macrophages seems to be mediated by monocyte chemoattractant protein 1 (MCP-1) or CCL2, because apoptosis and the production of MCP-1 mRNA occur simultaneously, but in different luteal cells, in a manner dependent on nuclear factor kappaB (NF-kappaB). In this study, we determined the mechanisms underlying the induction of these tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Likewise, we observed a similar response in the porcine CL with a dramatic and rapid increase in CCL2 mRNA only in CL with luteolytic capacity. Expression of CCL2 is regulated by AP-1 proteins in many cell types [42] including luteal cells [16]. A simplified scenario could be that lack of AP-1 activation due to lack of JUN induction leads to lack of CCL2 induction in CL without luteolytic capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, we observed a similar response in the porcine CL with a dramatic and rapid increase in CCL2 mRNA only in CL with luteolytic capacity. Expression of CCL2 is regulated by AP-1 proteins in many cell types [42] including luteal cells [16]. A simplified scenario could be that lack of AP-1 activation due to lack of JUN induction leads to lack of CCL2 induction in CL without luteolytic capacity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, PGF2α increases CYP19A1 [10] and CCL2 mRNA [9], and decreases STAR mRNA [7] only in CL with luteolytic capacity. All three of these genes ( CYP19A1 , STAR , and CCL2 ) are regulated by AP-1 transcriptional complexes [1620]. Therefore, this study was undertaken to determine whether AP-1 transcription factors are differentially regulated by PGF2α in porcine CL before and after acquisition of luteolytic capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Based on recent studies it also seems that the activation of JNK may contribute to the rapid induction of chemokines that occurs during luteal regression (Talbott et al, 2014;Walusimbi and Pate, 2013). Nagaosa et al (2008) demonstrated that treatment of rat luteal cell cultures with inhibitors of either JNK or AP-1 abolished increases in mRNA of the chemokine MCP-1. Likewise, the stimulatory effect of PGF 2␣ on expression of IL8 mRNA in vitro was prevented by an inhibitor of JNK signaling (Talbott et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…In normal resolution of the corpus luteum, macrophages accumulate and are responsible for clearance of the dying luteal cells. Here, induction of the monocyte/ macrophage chemoattractant chemokine (CCL12, MCP-1) from remaining viable cells apparently responding to the neighboring apoptotic cells seemed to mediate the attraction [8,9]. This may be a mechanism that applies in other situations in vivo.…”
mentioning
confidence: 86%